A tandem catalyst and a highly selective preparation method for low-carbon alcohols
Through the tandem catalyst system, the synergistic effect of K2O-CuO-ZnO-Fe2O3 and CuO-ZnO-Al2O3-ZrO2 was solved in the prior art, and the low selectivity of low carbon alcohols was achieved. Preparation of low-carbon alcohols with high conversion rate.
Patent Information
- Application Number
- CN202111015137.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-08-31
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2041-08-31
AI Technical Summary
In the prior art, the catalyst for hydrogenation of CO2 is low in selectivity and complex reactions, making it difficult to achieve efficient preparation.
The tandem catalyst system is adopted, including the first catalyst K2O-CuO-ZnO-Fe2O3 and the second catalyst CuO-ZnO-Al2O3-ZrO2, and the catalyst is filled by powder mixing, grinding mixing or twin-bed filling to achieve efficient synergistic effect of the catalyst.
The selectivity and conversion rate of low-carbon alcohols can be improved by hydrogenation of CO2. The selectivity of low-carbon alcohols can reach 25%, and the CO2 conversion rate is as high as 37%, achieving efficient utilization of catalysts.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and particularly relates to a tandem catalyst and a high-selectivity preparation method for low-carbon alcohols. Background Art
[0002] Since the new century, with the development of society, the emission of CO2 generated by the combustion of oil, coal and natural gas has continued to increase. Reducing CO2 emissions, seeking clean renewable energy and achieving carbon neutrality are urgent issues that need to be solved globally. Therefore, converting CO2 into high-value-added chemical energy has important application prospects.
[0003] Low-carbon mixed alcohols (low-carbon alcohols for short) can be directly used as high-quality power fuels, and due to the presence of oxygen in the alcohols, they burn more completely and are environmentally friendly fuels. Secondly, blending low-carbon alcohols with gasoline can expand gasoline supply and increase octane levels, and have excellent anti-explosion and anti-vibration properties. In addition to being used as fuels and additives as mentioned above, these low-carbon alcohols are also good solvents and industrial raw materials in chemical production. The conversion of CO2 hydrogenation into low-carbon alcohol liquid fuels is an extremely attractive research direction, but due to the complexity of the reactions involved, the highly selective preparation of low-carbon alcohols remains a severe challenge.
[0004] At present, the catalyst systems for preparing low-carbon alcohols from CO2 include Rh-based precious metal catalysts, Co-based catalysts, Cu-based catalysts, and Mo-based catalyst systems. Compared with syngas conversion, the selectivity of low-carbon alcohols for CO2 hydrogenation reactions is generally low due to the lower CO partial pressure. In general, the selectivity for low-carbon alcohols in current research reports on the preparation of low-carbon alcohols by CO2 hydrogenation is still low, so it is extremely challenging to develop cheap, highly active catalysts and new methods for directly preparing low-carbon alcohols by CO2 hydrogenation. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a tandem catalyst, which has a simple preparation method, low cost, easy promotion and use, and has good industrial application prospects; and based on the tandem catalyst, a highly selective preparation method of low-carbon alcohols is provided, which has simple operation, short reaction cycle, good repeatability, and can achieve sufficient utilization of CO2.
[0006] The present invention is achieved by adopting the following technical solutions:
[0007] A series catalyst comprising a first catalyst and a second catalyst;
[0008] The first catalyst comprises K2O-CuO-ZnO-Fe2O3, and the first catalyst accounts for 20%-80% of the total mass of the series catalysts;
[0009] The second catalyst comprises any one of CuO-ZnO-Al2O3-ZrO2, In2O3-mZrO2, xCuO-ZnO-ZrO2 and ZnO-Cr2O3-Al2O3 oxides, and the second catalyst accounts for 20-80% of the total mass of the series catalysts.
[0010] In a preferred embodiment, K in the first catalyst accounts for 0.6%-17.2% of the total mass of the K2O-CuO-ZnO-Fe2O3 catalyst; in a special embodiment, K in the first catalyst accounts for 3%, 3.1%, 4.7%, 6.2%, 6.4%, 10.7% or 17.2% of the total mass of the K2O-CuO-ZnO-Fe2O3 catalyst.
[0011] In a preferred embodiment, the loading method of the series catalyst includes any one of powder mixing, grinding mixing, and double-bed loading; in a further preferred embodiment, the powder mixing includes the following steps: directly shaking and mixing the first catalyst powder and the second catalyst powder at a mass ratio of (0.2-4):1, and then adding an inert material to shake and mix; in a further preferred embodiment, the grinding mixing includes the following steps: grinding the first catalyst powder and the second catalyst powder in a mortar at a mass ratio of (0.2-4):1 for 5-20 minutes, and then adding an inert material to shake and mix; in a further preferred embodiment, the double-bed loading includes the following steps: placing the first catalyst powder and the inert material in the lower layer, placing the mixture of the second catalyst powder and the inert material in the upper layer, and separating the upper and lower layers by a quartz wool layer; or placing the first catalyst powder and the inert material in the upper layer, placing the mixture of the second catalyst powder and the inert material in the lower layer, and separating the upper and lower layers by a quartz wool layer; in a further preferred embodiment, the mass of the inert material is 2-3 times the mass of the catalyst; in a further preferred embodiment, the inert material is quartz sand.
[0012] A highly selective preparation method for low-carbon alcohols comprises the following steps:
[0013] S1, Catalyst reduction and activation
[0014] The tandem catalyst is reduced in an atmosphere containing H2, and then activated in an atmosphere containing CO2 / H2 for 1-5h to obtain an activated catalyst;
[0015] S2, low carbon alcohol synthesis reaction
[0016] A mixed gas containing CO2 / H2 is introduced and the activated catalyst is used to react to obtain low-carbon alcohols.
[0017] In a preferred embodiment, in step S1, the reduction condition of the catalyst is to reduce the catalyst in an atmosphere containing H2 at 300-400°C for 1-3h; the activation condition of the catalyst is to activate the catalyst in an atmosphere containing CO2 / H2 at 300-350°C and 5MPa for 1-5h.
[0018] In a preferred embodiment, in step S2, the conditions for the low-carbon alcohol synthesis reaction are in a CO2 / H2 mixed gas at a reaction temperature of 280-330°C and a gas space velocity of 3000-6000g / s. -1 cat h -1 , the synthesis reaction is carried out under the condition of reaction pressure of 3-7MPa.
[0019] A special scheme, a highly selective preparation method of low-carbon alcohols, comprises the following steps:
[0020] S1, Catalyst reduction and activation
[0021] The tandem catalyst was reduced at 350 °C for 1 h in a H2 / Ar atmosphere, then cooled to 320 °C and heated at 15 mL min-1 using a CO2 / H2 mixed gas at 5 MPa. -1 Activate for 3h at a gas flow rate of
[0022] S2, low carbon alcohol synthesis reaction
[0023] In a CO2 / H2 mixed gas, the activated catalyst was used at 300°C, 5MPa, 3000mL g cat -1 h -1 The reaction of CO2 hydrogenation to prepare low-carbon alcohols is carried out under the conditions of.
[0024] The beneficial effects of the present invention are:
[0025] 1. The tandem catalyst of the present invention adopts a tandem catalytic strategy to construct a tandem catalytic system of a K-Cu-Fe-Zn main catalyst and a composite CO2 reduction (RWGS / high-temperature methanol synthesis) co-catalyst, and improves CO* / CH x The species coverage of O* can achieve the purpose of highly selective CO2 hydrogenation to produce low-carbon alcohols, which has very important academic and application value.
[0026] 2. The preparation method of the tandem catalyst of the present invention is simple, low-cost, easy to promote and use, and has good industrial application prospects.
[0027] 3. The highly selective preparation method of low-carbon alcohols of the present invention can catalytically hydrogenate CO2 into low-carbon alcohols with high selectivity. The operation is simple, the reaction cycle is short, and the repeatability is good. The selectivity of low-carbon alcohols can reach 25%, which is higher than that of a single catalyst. Moreover, the conversion rate of CO2 is as high as 37%, which can achieve sufficient utilization of CO2. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] 4.36 g Cu(NO3)2·3H2O, 8.08 g Fe(NO3)3·9H2O, and 4.96 g Zn(NO3)2·6H2O were weighed and dissolved in 100 mL deionized water to obtain an ion mixture; 27.6 g anhydrous potassium carbonate was weighed and dissolved in 100 mL deionized water; then the ion mixture was dripped evenly into the alkaline solution at a rate of 3 mL / min at a temperature of 80°C, and stirring was continued for 5 hours; finally, a first catalyst, i.e., K2O-CuO-ZnO-Fe2O3 catalyst, was obtained by washing with a certain amount of deionized water, filtering, drying, calcining, and subsequent impregnation with K, wherein the fixed K accounted for 3% of the total mass of the first catalyst;
[0031] 0.3 g of the first catalyst was mixed with 0.6 g of quartz sand to test the catalytic performance. The test results are shown in Table 1.
[0032] A highly selective preparation method for low-carbon alcohols, the catalytic conditions and steps are as follows:
[0033] S1, Catalyst reduction and activation
[0034] The tandem catalyst was reduced at 350 °C for 1 h in a H2 / Ar atmosphere, then cooled to 320 °C and heated at 15 mL min-1 using a CO2 / H2 mixed gas at 5 MPa. -1 Activate for 3h at a gas flow rate of
[0035] S2, low carbon alcohol synthesis reaction
[0036] In a CO2 / H2 mixed gas, the activated catalyst was used at 300°C, 5MPa, 3000mL g cat -1 h -1 The reaction of CO2 hydrogenation to prepare low-carbon alcohols is carried out under the conditions of.
[0037] Example 2
[0038] 7.29 g Zn(NO3)2·6H2O, 2.80 g Cr(NO3)3·9H2O, and 4.13 g Al(NO3)3·9H2O were weighed and dissolved in 50 mL deionized water to obtain an ion mixture; then 8.19 g ammonium carbonate was weighed and dissolved in 150 mL deionized water; the ammonium carbonate aqueous solution was added dropwise to the mixed ion mixture at 70°C and stirred for 3 hours; finally, the second catalyst, namely, ZnO-Cr2O3-Al2O3 catalyst, was obtained by centrifugation, washing, drying, and calcination;
[0039] 0.1 g of ZnO-Cr2O3-Al2O3 catalyst, 0.2 g of the first catalyst prepared in Example 1 and 0.6 g of quartz sand were loaded into a reaction tube in a powder mixing manner to test the catalytic performance. The catalytic test conditions were the same as in Example 1. The test results are shown in Table 1.
[0040] Example 3
[0041] 4.83 g Cu(NO3)2·3H2O, 2.98 g Zn(NO3)2·6H2O, 3.77 g Al(NO3)3·9H2O and 0.43 g Zr(NO3)4·5H2O were weighed and dissolved in 100 mL deionized water to obtain an ion mixture. Then 20.7 g potassium carbonate was weighed and dissolved in 100 mL deionized water. The ion mixture was heated at 80 °C at 3 mL min -1 Add the mixture dropwise into the potassium carbonate solution and continue stirring for 3 hours; finally, wash with deionized water, filter, dry and calcine to obtain the second catalyst, i.e., CuO-ZnO-Al2O3-ZrO2 catalyst;
[0042] 0.1 g of CuO-ZnO-Al2O3-ZrO2 catalyst, 0.2 g of the first catalyst prepared in Example 1 and 0.6 g of quartz sand were loaded into a reaction tube in a powder mixing manner to test the catalytic performance. The catalytic test conditions were the same as in Example 1. The test results are shown in Table 1.
[0043] Example 4
[0044] Weigh 0.60g Zn(NO3)2·6H2O and 5.80g Zr(NO3)4·5H2O and dissolve them in 100mL deionized water; weigh 3.06g ammonium carbonate and dissolve it in 100mL deionized water; add the ammonium carbonate aqueous solution dropwise to the Zn(NO3)2·6H2O at 70℃. 2+ , Zr 4+ The mixed solution was stirred for 3 hours, and then centrifuged, washed, dried, and calcined to obtain a second catalyst, namely, ZnO-ZrO2 catalyst;
[0045] 0.1 g of ZnO-ZrO2 catalyst, 0.2 g of the first catalyst prepared in Example 1 and 0.6 g of quartz sand were loaded into a reaction tube in a powder mixing manner to test the catalytic performance. The catalytic test conditions were the same as in Example 1. The test results are shown in Table 1.
[0046] Example 5
[0047] Weigh 2.01 g In(NO3)3·6H2O and dissolve it in 25 mL deionized water, then add 2.5 g commercially available mZrO2 and stir continuously for 1 h; add five-fold diluted ammonia water dropwise to the above dispersion until the pH is 9-10, continue stirring for 3 h, then centrifuge, dry and calcine to obtain the second catalyst, i.e., In2O3-mZrO2 catalyst;
[0048] 0.1 g of In2O3-mZrO2 catalyst, 0.2 g of the first catalyst prepared in Example 1 and 0.6 g of quartz sand were loaded into a reaction tube in a powder mixing manner to test the catalytic performance. The catalytic test conditions were the same as in Example 1. The test results are shown in Table 1.
[0049] Table 1 Catalytic performance test data of Examples 1-5
[0050]
[0051]
[0052] It can be seen from the data in Table 1 that, compared with the first catalyst prepared in Example 1, the tandem catalysts prepared in Examples 2-5 have improved selectivity and yield for low-carbon alcohols, and the tandem catalyst prepared in Example 3 has a better catalytic effect on low-carbon alcohols.
[0053] Example 6
[0054] 4.36 g Cu(NO3)2·3H2O, 8.08 g Fe(NO3)3·9H2O, and 4.96 g Zn(NO3)2·6H2O were weighed and dissolved in 100 mL deionized water to obtain an ion mixture; 27.6 g anhydrous potassium carbonate was weighed and dissolved in 100 mL deionized water; then the ion mixture was dripped evenly into the alkaline solution at a dripping rate of 3 mL / min at a temperature of 80°C, and stirring was continued for 5 hours; finally, the first catalyst, i.e., K2O-CuO-ZnO-Fe2O3 catalyst, was obtained by washing with 125 mL deionized water, filtering, drying, and calcining. The fixed K accounted for 4.7% of the total mass of the first catalyst;
[0055] 0.3 g of the first catalyst of this embodiment and 0.6 g of quartz sand were taken and loaded into a reaction tube in a powder mixing manner to test the catalytic performance. The catalytic test conditions were the same as those in Example 1. The test results are shown in Table 2.
[0056] Example 7
[0057] 4.83 g Cu(NO3)2·3H2O, 2.98 g Zn(NO3)2·6H2O, 3.77 g Al(NO3)3·9H2O and 0.43 g Zr(NO3)4·5H2O were weighed and dissolved in 100 mL deionized water to obtain an ion mixture; then 20.7 g potassium carbonate was weighed and dissolved in 100 mL deionized water, and the ion mixture was added dropwise to the potassium carbonate solution at a rate of 3 mL / min at 80°C, and stirring was continued for 3 h; finally, the second catalyst, namely, CuO-ZnO-Al2O3-ZrO2 catalyst, was obtained by washing with deionized water, filtering, drying and calcining.
[0058] 0.3 g of the second catalyst of this example and 0.6 g of quartz sand were taken and loaded into a reaction tube in a powder mixing manner to test the catalytic performance. The catalytic test conditions were the same as those in Example 1. The test results are shown in Table 2.
[0059] Example 8
[0060] The first catalyst of Example 6 and the second catalyst of Example 7 are compounded into a tandem catalyst, and the mass ratio of the first catalyst of Example 6 to the second catalyst of Example 7 is 2:1; 0.3g of the tandem catalyst of this example and 0.6g of quartz sand are taken and loaded into a reaction tube in a powder mixing manner, and the catalytic performance is tested. The catalytic test conditions are the same as those of Example 1, and the test results are shown in Table 2.
[0061] Example 9
[0062] The difference between this embodiment and embodiment 8 is that, in this embodiment, the mass ratio of the first catalyst of embodiment 6 to the second catalyst of embodiment 7 is 1:1.
[0063] Example 10
[0064] The difference between this embodiment and embodiment 8 is that, in this embodiment, the mass ratio of the first catalyst of embodiment 6 to the second catalyst of embodiment 7 is 1:2.
[0065] Table 2 Catalytic performance test data of Examples 6-10
[0066]
[0067] From the data in Table 2, it can be seen that the product of CO2 hydrogenation by CuO-ZnO-Al2O3-ZrO2 catalyst alone is mostly CO, and there is almost no selectivity for low-carbon alcohols. However, after being connected in series with K2O-CuO-ZnO-Fe2O3 catalyst, the selectivity and yield of single K2O-CuO-ZnO-Fe2O3 catalyst for low-carbon alcohols can be improved, indicating that there is a synergistic catalytic effect between the two catalysts; and the mass ratio of K2O-CuO-ZnO-Fe2O3 catalyst and CuO-ZnO-Al2O3-ZrO2 catalyst in the series catalyst has an effect on the selectivity of CO2 hydrogenation to low-carbon alcohols; when the mass ratio is 1:1, the CO2 conversion rate is 27.1%, the selectivity of low-carbon alcohols can reach a maximum of 24.6%, and the space-time yield of low-carbon alcohols is 42.0 mg g cat -1 h -1 .
[0068] Embodiment 11
[0069] 0.15 g of the first catalyst prepared in Example 6 and 0.15 g of the second catalyst prepared in Example 7 were weighed and ground in a mortar, and then loaded into a reaction tube by shaking and mixing with 0.6 g of quartz sand to test the catalytic performance. The catalytic test conditions were the same as those in Example 1. The test results are shown in Table 3.
[0070] Example 12
[0071] 0.15 g of the first catalyst prepared in Example 6 was mixed evenly with 0.3 g of quartz sand and placed in the lower layer; 0.15 g of the second catalyst prepared in Example 7 was mixed evenly with 0.3 g of quartz sand and placed in the upper layer; the upper layer and the lower layer were separated by a quartz wool layer;
[0072] The catalytic reaction was carried out by double-bed filling method to test the catalytic performance. The catalytic test conditions were the same as those in Example 1. The test results are shown in Table 3.
[0073] Embodiment 13
[0074] 0.15 g of the first catalyst prepared in Example 6 was mixed evenly with 0.3 g of quartz sand and placed on the upper layer; 0.15 g of the second catalyst prepared in Example 7 was mixed evenly with 0.3 g of quartz sand and placed on the lower layer; the upper layer and the lower layer were separated by a quartz wool layer;
[0075] The catalytic reaction was carried out by double-bed filling method to test the catalytic performance. The catalytic test conditions were the same as those in Example 1. The test results are shown in Table 3.
[0076] Embodiment 14
[0077] The difference between this embodiment and embodiment 11 is that the reaction pressure of this embodiment is 3 MPa. The test results are shown in Table 3.
[0078] Embodiment 15
[0079] The difference between this embodiment and embodiment 11 is that the reaction pressure of this embodiment is 7 MPa. The test results are shown in Table 3.
[0080] Example 16
[0081] The difference between this embodiment and embodiment 11 is that the reaction space velocity of this embodiment is 4600 mL g cat -1 h -1 , the test results are shown in Table 3.
[0082] Embodiment 17
[0083] The difference between this embodiment and embodiment 11 is that the reaction space velocity of this embodiment is 6000mL g cat -1 h -1 , the test results are shown in Table 3.
[0084] Table 3 Catalytic performance test data of Examples 11-17
[0085]
[0086] From the data in Table 3, we can see that the series connection of the first catalyst and the second catalyst has a greater impact on the performance of CO2 hydrogenation to low-carbon alcohols; the powder mixing method has the highest selectivity for low-carbon alcohols, and the grinding and mixing method with a closer distance can reduce the hydrogenation capacity of the overall catalyst, and the space-time yield of low-carbon alcohols reaches the highest, which can significantly improve the olefin selectivity without significantly reducing the selectivity of low-carbon alcohols; and the dual-bed loading reaction method has a greater disadvantage compared with the first two;
[0087] It shows that the proper distance between the two components in the tandem catalyst is more conducive to the transmission of intermediates and promotes the selectivity of the target product.
[0088] The catalytic performance of the ground catalyst under different pressure conditions shows that the preparation of low-carbon alcohols from CO2 requires appropriate pressure conditions. Increasing the reaction gas space velocity can increase the space-time yield of low-carbon alcohols.
[0089] Embodiment 18
[0090] 4.36 g Cu(NO3)2·3H2O, 8.08 g Fe(NO3)3·9H2O, and 4.96 g Zn(NO3)2·6H2O were weighed and dissolved in 100 mL deionized water to obtain an ion mixture; 27.6 g anhydrous potassium carbonate was weighed and dissolved in 100 mL deionized water; then the ion mixture was dripped evenly into the alkaline solution at a rate of 3 mL / min at 80°C, and stirring was continued for 5 h; finally, the first catalyst, i.e., K2O-CuO-ZnO-Fe2O3 catalyst, was obtained by washing with 50 mL deionized water, filtering, drying, and calcining. The fixed K accounted for 10.7% of the total mass of the first catalyst;
[0091] 0.3 g of the first catalyst of this embodiment and 0.6 g of quartz sand were taken and loaded into a reaction tube in a powder mixing manner to test the catalytic performance. The catalytic test conditions were the same as those in Example 1. The test results are shown in Table 4.
[0092] Embodiment 19
[0093] 0.15 g of the first catalyst prepared in Example 18, 0.15 g of the second catalyst prepared in Example 7 and 0.6 g of quartz sand were weighed and loaded into a reaction tube in a powder mixing manner to test the catalytic performance. The catalytic test conditions were the same as in Example 1. The test results are shown in Table 4.
[0094] Embodiment 20
[0095] Weigh 4.36g Cu(NO3)2·3H2O, 8.08g Fe(NO3)3·9H2O, 4.96g Zn(NO3)2·6H2O and dissolve them in 100mL deionized water to obtain an ion mixture; weigh 27.6g anhydrous potassium carbonate and dissolve it in 100mL deionized water. Then, drip the ion mixture into the alkali solution at a rate of 3mL / min at 80°C and continue stirring for 5h; directly filter, dry and calcine without washing to obtain the first catalyst, namely K2O-CuO-ZnO-Fe2O3 catalyst, in which fixed K accounts for 17.2% of the total mass of the first catalyst;
[0096] 0.3 g of the first catalyst of this embodiment and 0.6 g of quartz sand were taken and loaded into a reaction tube in a powder mixing manner to test the catalytic performance. The catalytic test conditions were the same as those in Example 1. The test results are shown in Table 4.
[0097] Embodiment 21
[0098] 0.15 g of the first catalyst prepared in Example 20, 0.15 g of the second catalyst prepared in Example 7 and 0.6 g of quartz sand were weighed and loaded into a reaction tube in a powder mixing manner to test the catalytic performance. The catalytic test conditions were the same as in Example 1. The test results are shown in Table 4.
[0099] Table 4 Catalytic performance test data of Examples 18-21
[0100]
[0101] From the data in Table 4, it can be seen that the K content can significantly affect the CO2 conversion rate and product selectivity; after the first catalyst with different K contents is composited with the second catalyst powder, the selectivity and space-time yield of low-carbon alcohols are improved, which illustrates the universality of the tandem catalytic strategy.
[0102] Embodiment 22
[0103] 4.36 g Cu(NO3)2·3H2O, 8.08 g Fe(NO3)3·9H2O, and 4.96 g Zn(NO3)2·6H2O were weighed and dissolved in 100 mL deionized water to obtain an ion mixture; 27.6 g anhydrous potassium carbonate was weighed and dissolved in 100 mL deionized water; then the ion mixture was dripped evenly into the alkaline solution at a dripping rate of 3 mL / min at a temperature of 80°C, and stirring was continued for 5 hours; finally, the first catalyst, i.e., K2O-CuO-ZnO-Fe2O3 catalyst, was obtained by washing with 140 mL deionized water, filtering, drying, and calcining. The fixed K accounted for 3.1% of the total mass of the first catalyst;
[0104] 0.15 g of the first catalyst prepared in this example and 0.15 g of the second catalyst prepared in Example 7 were weighed and ground in a mortar, and then loaded into a reaction tube with 0.6 g of quartz sand by shaking and mixing. The catalytic performance was tested. The catalytic test conditions were the same as those in Example 1. The test results are shown in Table 5.
[0105] Embodiment 23
[0106] 4.36 g Cu(NO3)2·3H2O, 8.08 g Fe(NO3)3·9H2O, and 4.96 g Zn(NO3)2·6H2O were weighed and dissolved in 100 mL deionized water to obtain an ion mixture; 27.6 g anhydrous potassium carbonate was weighed and dissolved in 100 mL deionized water; then the ion mixture was dripped evenly into the alkaline solution at a dripping rate of 3 mL / min at a temperature of 80°C, and stirring was continued for 5 hours; finally, the first catalyst, i.e., K2O-CuO-ZnO-Fe2O3 catalyst, was obtained by washing with 90 mL deionized water, filtering, drying, and calcining. The fixed K accounted for 6.4% of the total mass of the first catalyst;
[0107] 0.3 g of the first catalyst prepared in this example and 0.6 g of quartz sand were weighed and loaded into a reaction tube by shaking and mixing, and the catalytic performance was tested. The catalytic test conditions were the same as those in Example 1. The test results are shown in Table 5.
[0108] Embodiment 24
[0109] 0.15 g of the first catalyst prepared in Example 23 and 0.15 g of the second catalyst prepared in Example 7 were weighed and ground in a mortar, and then loaded into a reaction tube by shaking and mixing with 0.6 g of quartz sand to test the catalytic performance. The catalytic test conditions were the same as those in Example 1. The test results are shown in Table 5.
[0110] Embodiment 25
[0111] 0.15 g of the first catalyst prepared in Example 18 and 0.15 g of the second catalyst prepared in Example 7 were weighed and ground in a mortar, and then loaded into a reaction tube by shaking and mixing with 0.6 g of quartz sand to test the catalytic performance. The catalytic test conditions were the same as in Example 1. The test results are shown in Table 5.
[0112] Table 5 Catalytic performance test data of Examples 22-25
[0113]
[0114] From the data in Table 5, it can be seen that the content of K can significantly affect the conversion rate and product selectivity of the grinding mixed tandem catalyst. The trend of the change in the yield of low-carbon alcohols of the grinding mixed tandem catalysts with different K contents is similar to that of the first catalyst alone, indicating that the first catalyst is dominant in the reaction performance of the tandem catalyst; the improvement in the catalytic performance of these grinding mixed tandem catalysts also illustrates the universality of the tandem catalytic strategy.
[0115] Embodiment 26
[0116] 4.36 g Cu(NO3)2·3H2O, 8.08 g Fe(NO3)3·9H2O, and 4.96 g Zn(NO3)2·6H2O were weighed and dissolved in 100 mL deionized water to obtain an ion mixture; 27.6 g anhydrous potassium carbonate was weighed and dissolved in 100 mL deionized water; then the ion mixture was dripped evenly into the alkaline solution at a rate of 3 mL / min at a temperature of 80°C, and stirring was continued for 5 hours; finally, a first catalyst, i.e., K2O-CuO-ZnO-Fe2O3 catalyst, was obtained by washing with a certain amount of deionized water, filtering, drying, and calcining. The fixed K accounted for 6.2% of the total mass of the first catalyst;
[0117] 0.3 g of the first catalyst prepared in this example and 0.6 g of quartz sand were weighed and loaded into a reaction tube by shaking and mixing, and the catalytic performance was tested. The catalytic test conditions were the same as those in Example 1. The test results are shown in Table 6.
[0118] Embodiment 27
[0119] Weigh 0.60g Zn(NO3)2·6H2O and 5.80g Zr(NO3)4·5H2O and dissolve them in 100mL deionized water; weigh 3.06g ammonium carbonate and dissolve it in 100mL deionized water; add the ammonium carbonate aqueous solution dropwise to the Zn(NO3)2·6H2O at 70℃. 2+ , Zr 4+ The mixed solution was stirred for 3 hours, and then centrifuged, washed, dried, and calcined to obtain a second catalyst, namely, ZnO-ZrO2 catalyst;
[0120] 0.3 g of the second catalyst of this example and 0.6 g of quartz sand were mixed in a powder form and loaded into a reaction tube to test the catalytic performance. The catalytic test conditions were the same as those of Example 1. The test results are shown in Table 6.
[0121] Embodiment 28
[0122] 0.1 g of the second catalyst prepared in Example 27, 0.2 g of the first catalyst prepared in Example 26 and 0.6 g of quartz sand were mixed in a powder form and loaded into a reaction tube. The catalytic test conditions were as above, and the specific test performance is shown in Table 6.
[0123] Embodiment 29
[0124] Take 18.81 mg Cu(NO3)2·3H2O, 0.60 g Zn(NO3)2·6H2O and 5.80 g Zr(NO3)4·5H2O and dissolve them in 100 mL deionized water; add 0.32 mol·L -1 Ammonium carbonate aqueous solution was added dropwise to Zn at 70 °C. 2+ , Zr 4+ The mixed solution was stirred for 3 hours until the pH value reached 9; then centrifuged, washed, dried and calcined to obtain a second catalyst, namely, a CuO-ZnO-ZrO2 catalyst, wherein the fixed Cu accounted for 0.5% of the total mass of the second catalyst;
[0125] 0.3 g of the second catalyst of this example and 0.6 g of quartz sand were mixed in a powder form and loaded into a reaction tube to test the catalytic performance. The catalytic test conditions were the same as those of Example 1. The test results are shown in Table 6.
[0126] Embodiment 30
[0127] 0.1 g of the second catalyst prepared in Example 29, 0.2 g of the first catalyst prepared in Example 26 and 0.6 g of quartz sand were mixed in a powder form and loaded into a reaction tube to test the catalytic performance. The catalytic test conditions were the same as those in Example 1. The test results are shown in Table 6.
[0128] Embodiment 31
[0129] 0.15 g of the second catalyst prepared in Example 29, 0.15 g of the first catalyst prepared in Example 26 and 0.6 g of quartz sand were loaded into a reaction tube in a powder mixing manner to test the catalytic performance. The catalytic test conditions were the same as in Example 1. The test results are shown in Table 6.
[0130] Embodiment 32
[0131] Take 26.39 mg Cu(NO3)2·3H2O, 0.60 g Zn(NO3)2·6H2O and 5.80 g Zr(NO3)4·5H2O and dissolve them in 100 mL deionized water. -1 Ammonium carbonate aqueous solution was added dropwise to Zn at 70 °C. 2+ , Zr 4+ The mixed solution was stirred for 3 hours until the pH value reached 9; then centrifuged, washed, dried and calcined to obtain a second catalyst, namely, a CuO-ZnO-ZrO2 catalyst, wherein the fixed Cu accounted for 0.7% of the total mass of the second catalyst;
[0132] 0.3 g of the second catalyst of this example and 0.6 g of quartz sand were mixed in a powder form and loaded into a reaction tube to test the catalytic performance. The catalytic test conditions were the same as those of Example 1. The test results are shown in Table 6.
[0133] Embodiment 33
[0134] 0.1 g of the second catalyst prepared in Example 32, 0.2 g of the first catalyst prepared in Example 26 and 0.6 g of quartz sand were mixed in a powder form and loaded into a reaction tube to test the catalytic performance. The catalytic test conditions were the same as in Example 1. The test results are shown in Table 6.
[0135] Embodiment 34
[0136] Take 37.82 mg Cu(NO3)2·3H2O, 0.60 g Zn(NO3)2·6H2O and 5.80 g Zr(NO3)4·5H2O and dissolve them in 100 mL deionized water. -1 Ammonium carbonate aqueous solution was added dropwise to Zn at 70 °C. 2+ , Zr 4+ The mixture was stirred for 3 h until the pH reached 9. Then, it was centrifuged, washed, dried, and calcined to obtain a second catalyst, namely, a CuO-ZnO-ZrO2 catalyst, wherein the fixed Cu accounted for 1% of the total mass of the second catalyst;
[0137] 0.3 g of the second catalyst of this example and 0.6 g of quartz sand were mixed in a powder form and loaded into a reaction tube to test the catalytic performance. The catalytic test conditions were the same as those of Example 1. The test results are shown in Table 6.
[0138] Embodiment 35
[0139] 0.15 g of the second catalyst prepared in Example 34, 0.15 g of the first catalyst prepared in Example 26 and 0.6 g of quartz sand were mixed in a powder form and loaded into a reaction tube to test the catalytic performance. The catalytic test conditions were the same as in Example 1. The test results are shown in Table 6.
[0140] Table 6 Catalytic performance test data of Examples 26-35
[0141]
[0142]
[0143] In Table 6, Examples 27, 29, 32, and 34 contain a small amount of dimethyl ether which is not shown in the table, and the selectivity of the dimethyl ether product is <1%.
[0144] From the data in Table 6, it can be seen that when the ZnO-ZrO2 catalyst is loaded with a small amount of Cu, the methanol yield presents a volcano-shaped curve that first increases and then decreases; after being compounded with the first catalyst of Example 26, the space-time yield of low-carbon alcohols of the corresponding tandem catalyst is positively correlated with the methanol yield of the CuO-ZnO-ZrO2 catalyst alone, indicating that the methanol produced in the methanol synthesis catalyst can promote the synthesis of low-carbon alcohols in the tandem catalytic system.
[0145] The foregoing description of specific exemplary embodiments of the present invention is for the purpose of illustration and demonstration. These descriptions are not intended to limit the present invention to the precise form disclosed, and it is clear that many changes and variations can be made based on the above teachings. The purpose of selecting and describing the exemplary embodiments is to explain the specific principles of the present invention and its practical application, so that those skilled in the art can realize and utilize various different exemplary embodiments of the present invention and various different selections and changes. The scope of the present invention is intended to be limited by the claims and their equivalents.
Claims
1. An application of a tandem catalyst, characterized in that: The tandem catalyst is used to produce low-carbon alcohols by hydrogenation of CO2; The series catalyst includes a first catalyst and a second catalyst; The first catalyst is K2O-CuO-ZnO-Fe2O3, and the first catalyst accounts for 20%-80% of the total mass of the series catalyst; K in the first catalyst accounts for 0.6%-17.2% of the total mass of the K2O-CuO-ZnO-Fe2O3 catalyst; The second catalyst is any one of CuO-ZnO-Al2O3-ZrO2, In2O3-mZrO2 and ZnO-Cr2O3-Al2O3 oxides, and the second catalyst accounts for 20-80% of the total mass of the series catalysts.
2. The use of the tandem catalyst according to claim 1, characterized in that: The loading method of the series catalyst includes any one of powder mixing, grinding mixing and double-bed loading.
3. The use of the tandem catalyst according to claim 2, characterized in that: The powder mixing comprises the following steps: directly shaking and mixing the first catalyst powder and the second catalyst powder at a mass ratio of (0.2-4):1, and then adding an inert material and shaking and mixing.
4. The use of the tandem catalyst according to claim 2, characterized in that: The grinding and mixing comprises the following steps: grinding the first catalyst powder and the second catalyst powder together in a mortar at a mass ratio of (0.2-4):1 for 5-20 minutes, and then adding an inert material and shaking and mixing.
5. The use of the tandem catalyst according to claim 2, characterized in that: The double-bed loading comprises the following steps: placing the first catalyst powder and the inert material in the lower layer, placing the mixture of the second catalyst powder and the inert material in the upper layer, and the upper layer and the lower layer are separated by a quartz wool layer; Alternatively, the first catalyst powder and the inert material are placed in an upper layer, and a mixture of the second catalyst powder and the inert material is placed in a lower layer, and the upper layer and the lower layer are separated by a quartz wool layer.
6. The use of the tandem catalyst according to any one of claims 3 to 5, characterized in that: The mass of the inert material is 2-3 times the mass of the catalyst.
7. The use of the tandem catalyst according to claim 1, characterized in that: The steps include: S1, Reduction and activation of catalyst The tandem catalyst is reduced in an atmosphere containing H2, and then activated in an atmosphere containing CO2 / H2 for 1-5h to obtain an activated catalyst; S2, low carbon alcohol synthesis reaction A mixed gas containing CO2 / H2 is introduced and the activated catalyst is used to react to obtain low-carbon alcohols.
8. The use of the tandem catalyst according to claim 7, characterized in that: In step S1, the reduction condition of the catalyst is in an atmosphere containing H2 at 300-400°C for 1-3h; the activation condition of the catalyst is in an atmosphere containing CO2 / H2 at 300-350°C and 5MPa for 1-5h.
9. The use of the tandem catalyst according to claim 7, characterized in that: In step S2, the conditions for the low-carbon alcohol synthesis reaction are in a CO2 / H2 mixed gas at a reaction temperature of 280-330°C and a gas space velocity of 3000-6000 mL / min. cat -1 h -1 , the synthesis reaction is carried out under the condition of reaction pressure of 3-7MPa.
Citation Information
Patent Citations
Preparation method of methanol catalyst by catalytic hydrogenation of high specific surface CO2
CN106883097A
Method for directly preparing low-carbon alcohol and co-producing gasoline through CO2 hydrogenation
CN112430472A